Peredaran Matahari dan Bulan Dalam Wawasan Al-Qur’an (Kajian Tafsir Ilmi) - Mitra, Andi; Amin, Rosmini; Ghany, Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The sun and moon are celestial bodies that play an important role in human life. The sun and moon move in a way called their orbit, which rotates on their axis, the moon orbits the earth and the sun, while orbiting the center of the Milky Way. Astronomers have found many continuity of information conveyed by the Qur'an, especially about the orbit of the moon and the sun which is widely conveyed by the Qur'an. The Qur'an discusses many concepts of the orbit of the moon and the sun from several verses in the Qur'an. The research study on this research concept uses scientific interpretation as a support in understanding the concept of orbit according to that in the Qur'an.